Extragenital Canine Transmissible Venereal Tumor with Metastasis to Regional Lymph Node - Marques Cunha, Kayana; Luz Lopes Rocha , Brizza Zorayd; César de Oliveira , Luanda Pâmela; Lira Borges , Ismael; Galvão Alves Rodrigues , Ramon Tadeu; Brilhante Bezerra, José Artur; Azevedo de Paula Antunes , João Marcelo; Dantas Filgueira, Kilder (Acta Scientiae Veterinariae, 2024)
Background: Canine venereal transmissible tumor (TVT) is a neoplasia with high incidence and wide distribution across Brazil. The genital mucosa is the most affected site, and the coitus is the main transmission route. However, the extragenital form of the disease can occur, with or without concomitant involvement of the external genitalia. The observation of metastasis is uncommon but can occur in lymph nodes, skin, muscle, oral cavity, nasal cavity, brain, eyes, spleen, liver, and abdominal cavity. Thus, the objective of this study was to report 2 cases of primary extragenital canine TVT with regional lymph node metastasis. Cases: Case 1. A 2-year-old mixed-breed male dog with outdoor access and, a history of a nodule in the oral mucosa, with an evolution time of 2 months was evaluated. During the physical examination, it was observed a nodule on the left side of the lower lip mucosa, which was friable, with an irregular and ulcerated surface, and presenting bloody discharge. Additionally, the left submandibular lymph node was hypertrophied. Complete blood count (CBC), serum biochemistry, and abdominal ultrasonography were normal. The nodule and lymph node cytology were compatible with plasmacytoid-like TVT. Case 2. Another 2-year-old mixed-breed male dog, with outdoor access presenting increased nasal planum volume, weight loss, dyspnea, cough, and epistaxis for the past 2 weeks was attended. During the examination, a nodule in the cranial part of the left nostril was observed. The volume of the nasal planum was increased, and the oral cavity presented ulceration in the hard palate. Moreover, the left submandibular lymph node was hypertrophied. CBC revealed normochromic normocytic anemia and intraplatelet inclusions compatible with Anaplasma platys. Radiography revealed increased radiopacity of the sinuses. The cytology of the lesions of the nostril and hard palate, and lymph node were compatible with mixed-type TVT. Both animals were treated with sulfate vincristine (0.7 mg/m2, IV, weekly, for 4 weeks), ivermectin (0.6 mg/kg, SC, weekly, for 4 weeks), and calf thymus lysate (4 mL/animal, PO, every 24 h, for 4 weeks). Case 2 was also treated with doxycycline (10 mg/kg, PO, BID, for 4 weeks) for anaplasmosis. The animals presented a good therapeutic response, with resolution of the clinical abnormalities after 4 weeks of treatment. Discussion: The TVT is considered a neoplasm of round cells and is mainly transmitted through sexual contact. Therefore, animals with outdoor access are at higher risk of acquiring this disease. Canine TVT usually has benign behavior, and metastases are observed at a rate of 1 to 15% of the cases, being associated with some factors, such as long permanence of the tumor in the animal, immunosuppression, and advanced age. The extragenital presentations of TVT affect mainly the nasal cavity (11%), followed by the skin (10%) and oral cavity (5%). Regarding the therapy, the procedure of choice is chemotherapy, with vincristine sulfate being the first choice of antineoplastic drug, and the primary extragenital forms of TVT with metastasis present a good response to this treatment. Extragenital TVT should be included as a differential diagnosis for nodules in the oral and nasal cavities of dogs, with the possibility of regional metastasis and the absence of primary genital lesions. Keywords: reproductive neoplasm, canine transmissible venereal tumor, extragenital presentation, lymphatic metastasis. Título: Tumor venéreo transmissível canino extragenital com metástase para linfonodo regional Descritores: neoplasia reprodutiva, tumor venéreo transmissível canino, apresentação extragenital, metástase linfática.